Recent Advances in Amorphous Solid Dispersions: Preformulation, Formulation Strategies, Technological Advancements and Characterization - Srushti Tambe; Divya Jain; Sai Kishore Meruva; Gopinath Rongala; Abhishek Juluri; Girish Nihalani; Hemanth Kumar Mamidi; Pavan Kumar Nukala; Pradeep Kumar Bolla (MDPI AG, 2022)
Amorphous solid dispersions (ASDs) are among the most popular and widely studied solubility enhancement techniques. Since their inception in the early 1960s, the formulation development of ASDs has undergone tremendous progress. For instance, the method of preparing ASDs evolved from solvent-based approaches to solvent-free methods such as hot melt extrusion and Kinetisol®. The formulation approaches have advanced from employing a single polymeric carrier to multiple carriers with plasticizers to improve the stability and performance of ASDs. Major excipient manufacturers recognized the potential of ASDs and began introducing specialty excipients ideal for formulating ASDs. In addition to traditional techniques such as differential scanning calorimeter (DSC) and X-ray crystallography, recent innovations such as nano-tomography, transmission electron microscopy (TEM), atomic force microscopy (AFM), and X-ray microscopy support a better understanding of the microstructure of ASDs. The purpose of this review is to highlight the recent advancements in the field of ASDs with respect to formulation approaches, methods of preparation, and advanced characterization techniques